2007
DOI: 10.1074/jbc.m704756200
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent Neuroprotective Protein Constitutes a Novel Element in the SWI/SNF Chromatin Remodeling Complex

Abstract: Complete deficiency in activity-dependent neuroprotective protein (ADNP), a heterochromatin 1-binding protein, results in dramatic changes in gene expression, neural tube closure defects, and death at gestation day 9 in mice. To further understand the cellular roles played by ADNP, the HEK293 human embryonic kidney cell line that allows efficient transfection with recombinant DNA was used as a model for the identification of ADNP-interacting proteins. Recombinant green fluorescent protein (GFP)-ADNP was locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 29 publications
2
117
0
1
Order By: Relevance
“…Consistent with these findings, recent work has shown that ADNP differentially interacts with chromatin to regulate essential genes [25][26][27][28] and ADNP was found to play a role in neurite outgrowth [18], potentially as part of a chromatin re-modeling complex, interacting with essential proteins like BRG1 and heterochromatin protein 1 alpha, as well as by direct activity in the neuronal cytoplasm [18,25]. The essential role of ADNP in neuro-differentiation and potentially in neuronal injury is exemplified in that, complete ADNP deficiency is embryonic lethal at the time of neural tube closure [29].…”
Section: Activity-dependent Neuroprotective Protein (Adnp)mentioning
confidence: 57%
“…Consistent with these findings, recent work has shown that ADNP differentially interacts with chromatin to regulate essential genes [25][26][27][28] and ADNP was found to play a role in neurite outgrowth [18], potentially as part of a chromatin re-modeling complex, interacting with essential proteins like BRG1 and heterochromatin protein 1 alpha, as well as by direct activity in the neuronal cytoplasm [18,25]. The essential role of ADNP in neuro-differentiation and potentially in neuronal injury is exemplified in that, complete ADNP deficiency is embryonic lethal at the time of neural tube closure [29].…”
Section: Activity-dependent Neuroprotective Protein (Adnp)mentioning
confidence: 57%
“…Our results placed ADNP at a crucial point of gene regulation, repressing potential endoderm genes and enhancing genes associated with organogenesis/neurogenesis. Immunoprecipitation experiments showed interactions with heterochromatin protein1 (HP1 ), [100] and with BRG1, BAF250a, and BAF170, all components of the SWI/SNF (mating type switching/sucrose nonfermenting) chromatin remodeling complex [101]. Together, our results place ADNP in a chromatin remodeling epigenetic role in neurodifferentiation and neuroplasticity.…”
Section: Activity-dependent Neuroprotective Pr-otein (Adnp) Tauopathmentioning
confidence: 77%
“…Immunoprecipitation with specific antibodies identified ADNP interacting proteins including BRG1, BAF250a, and BAF170, all components of the SWI/SNF (mating type switching/sucrose nonfermenting) chromatin remodeling complex. ADNP short hairpin RNA down-regulation resulted in microtubule reorganization and changes in cell morphology including reduction in cell process formation and cell number [39], [40].…”
Section: Introductionmentioning
confidence: 99%